2013
DOI: 10.1080/10496475.2013.790331
|View full text |Cite
|
Sign up to set email alerts
|

In VitroFlowering and Micropropagation ofHyptis suaveolens(Linn.) Poit.—An Important Medicinal Herb

Abstract: An optimized protocol for micropropagation of Hyptis suaveolens was developed. A 100% shoot regeneration frequency and 16.9 shoots per node explant were achieved on Murashige and Skoog medium (MS) containing 1.0 mg.L −1 N6-benzylaminopurine (BAP) and 0.5 mg.L −1 gibberellic acid (GA 3 ). Node explants of microshoots could be induced for proliferation of a large number of harvestable shoots on the same medium. The shoots developed in vitro inflorescences and 8.5 flowers per shoot on MS medium supplemented with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The effect of GA 3 alone or in combination with cytokinins or auxins have been explored in other Lamiaceae species, such as the study by Mandal (2013) [55] which showed that the addition of 4.44 µM BAP and 1.44 µM GA 3 to the culture medium is favorable for the multiplication of Hyptis suaveolens and allows a total regeneration of the explants. In addition, Samantaray et al ( 2013) [56] obtained a maximum regeneration rate of Vitex trifolia explants in the medium containing 1.14 µM GA 3 , 0.54 µM NAA, and 271.5 µM Adenine.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of GA 3 alone or in combination with cytokinins or auxins have been explored in other Lamiaceae species, such as the study by Mandal (2013) [55] which showed that the addition of 4.44 µM BAP and 1.44 µM GA 3 to the culture medium is favorable for the multiplication of Hyptis suaveolens and allows a total regeneration of the explants. In addition, Samantaray et al ( 2013) [56] obtained a maximum regeneration rate of Vitex trifolia explants in the medium containing 1.14 µM GA 3 , 0.54 µM NAA, and 271.5 µM Adenine.…”
Section: Discussionmentioning
confidence: 99%